A Respectful Workplace Culture to Address Nurse-to-Nurse Incivility: A Descriptive Qualitative Study - Mongalo, Kgaogelo Jessica; Leech, Ronell; Heyns, Tanya (Africa Journal of Nursing and Midwifery, 2025)
ntroduction: Almost 90% of nurses are affected by incivility in their workplace, which has negative outcomes for nurses, the organisation, and patients. Workplace culture is a key determinant of incivility because it shapes how employees perceive, feel, act, and relate to one another within the organisation. Research objective: To explore nurses’ perceptions of encouraging and sustaining a workplace culture that addresses nurse-to-nurse incivility. Materials and methods: A descriptive qualitative design was used to describe nurse-to-nurse incivility. Eight nurses working in a female medical ward in an academic hospital were interviewed individually and face-to-face. These nurses were selected through purposive and snowball sampling. Nurses voluntarily signed a consent form based on the information provided by the researcher. The data was analysed using content analysis. Findings: Interview results showed that a respectful workplace culture to address nurse-to-nurse incivility could be achieved through team interventions such as team building, weekly/monthly meetings to discuss staff problems; training interventions such as orientation on appropriate behaviour at work, teaching staff about coping mechanisms, in-service training; and managerial interventions such as swift managerial action against workplace incivility, support to victims and perpetrators by Employee Wellness unit, and decisive resolution of incivility fair and just manner. Conclusion: It was evident that a disrespectful workplace culture caused by nurse-to-nurse incivility is still prevalent in the designated academic hospital, with negative consequences for nurses, patients, and the organisation. Hospital management and nurse managers should implement the recommendations to create a respectful workplace culture.